HAM sebagai Parameter Legitimasi Kebijakan Publik dalam Negara Hukum - Ni Putu Rai Yuliartini; Dewa Gede Sudika Mangku; Rina Khairani Pancaningrum; Gede Sariasa; David Greacy Geovanie (Unram Law Review, 2026)
Human rights constitute a fundamental principle in a democratic state governed by the rule of law and function both as a limit and a benchmark for the legitimacy of the exercise of state power in the formulation of public policies. In practice, however, public policies are often driven more by political considerations, security concerns, and administrative efficiency, which may lead to the neglect of human rights protection standards. This study aims to analyze the role of human rights as a parameter for the legitimacy of public policies within the framework of a rule-of-law state and to assess their implications for the protection of citizens’ rights.The research employs a normative legal research method, using statutory, conceptual, and analytical approaches to national and international human rights instruments. The findings indicate that the legitimacy of public policies cannot be determined solely by their legal-formal validity, but must also be assessed based on their conformity with human rights principles, such as legality, proportionality, non-discrimination, and the protection of fundamental rights. Public policies that are not grounded in human rights standards risk producing excessive restrictions on rights and undermining the principles of the rule of law. Furthermore, international human rights instruments, particularly the International Covenant on Civil and Political Rights (ICCPR), provide an essential normative framework for evaluating the lawfulness of state-imposed limitations on rights. Accordingly, this study emphasizes that human rights must be positioned as the primary parameter in the formulation and implementation of public policies to ensure a balance between public interests and the protection of individual rights in a state governed by the rule of law.